2017
DOI: 10.2147/rmhp.s130341
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden of hospitalizations of Medicare beneficiaries with heart failure

Abstract: ObjectiveThe objective of this study was to assess the costs associated with the hospitalization and the cumulative 30-, 60-, and 90-day readmission rates in a cohort of Medicare beneficiaries with heart failure (HF).MethodsThis was a retrospective, observational study based on data from the national 5% sample of Medicare beneficiaries. Inpatient data were gathered for Medicare beneficiaries with at least one HF-related hospitalization between July 1, 2005, and December 31, 2011. The primary end point was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
105
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(124 citation statements)
references
References 13 publications
2
105
1
2
Order By: Relevance
“…This chronic condition consumes signi icant healthcare resources and is associated with repeated ER visits and hospitalizations, and high rates of readmission. In the United States, CHF is one of the Medicare readmission penalty diseases; the average cost of a single hospitalization for a Medicare recipient is $14,631, with a median length-of-stay of ive days [20]. Data demonstrate that 40.2% of Medicare patients with CHF are readmitted within 90 days of a prior hospital discharge [20].…”
Section: Congestive Heart Failure (Chf) Managementmentioning
confidence: 99%
“…This chronic condition consumes signi icant healthcare resources and is associated with repeated ER visits and hospitalizations, and high rates of readmission. In the United States, CHF is one of the Medicare readmission penalty diseases; the average cost of a single hospitalization for a Medicare recipient is $14,631, with a median length-of-stay of ive days [20]. Data demonstrate that 40.2% of Medicare patients with CHF are readmitted within 90 days of a prior hospital discharge [20].…”
Section: Congestive Heart Failure (Chf) Managementmentioning
confidence: 99%
“…Heart failure constitutes a large portion of this spectrum with close to 6 million adults affected in the US [1]. That number is expected to increase over the next 15 years with CVD-related costs projected to reach up to $1.1 trillion, a large portion of which can be attributed to heart failure (HF) rehospitalizations [2]. Clinical trials have shown that HF patients have 90-day readmission rates of nearly 41% with a mean per-patient expense of $16,000 [2].…”
Section: Introductionmentioning
confidence: 99%
“…That number is expected to increase over the next 15 years with CVD-related costs projected to reach up to $1.1 trillion, a large portion of which can be attributed to heart failure (HF) rehospitalizations [2]. Clinical trials have shown that HF patients have 90-day readmission rates of nearly 41% with a mean per-patient expense of $16,000 [2]. Further, the average lifetime expense of each HF patient is roughly $83,980, 80% of which is thought to be accumulated during these hospitalizations [2].…”
Section: Introductionmentioning
confidence: 99%
“…HF implies a substantial burden not only for patients and but also for healthcare systems in developed countries [7]. HF is the most common reason for hospital admission in patients above 65 years old [8]. For instance, in the USA the number of HF hospitalizations tripled from 1.27 to 3.86 million between 1979 and 2004 [9,10].…”
Section: Introductionmentioning
confidence: 99%